P491 Scedosporium Apiospermum brain abscess in an immunocompetent host: Rare case from Southern India. (20th September 2022) - Joshi, Divya; Sridharan, Sowmya; Gopalakrishnan, Ram
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM:   Objectives/Introduction: Scedosporium apiospermum is a filamentous fungus that causes a broad spectrum of diseases in an immunocompromised host involving the lungs, skin, bones, eyes, joints, and the central nervous system. It is a rare cause of fungal brain abscess, more so in an immunocompetent individual. Here, we report a case of brain abscess in an immunocompetent host caused by S. apiospermum . Methods: A 78-year-old retired railway officer from Chennai, presented to our hospital on May 4, 2022, with a 3-month history of weakness, gait instability followed by difficulty in walking, and left hemiparesis. In all, 20 days before the presentation, he had an episode of generalized tonic-clonic seizure with worsening of his neurological state resulting in bed-bound status. His medical history included Pemphigus vulgaris for which he was on topical treatment, well-controlled diabetes mellitus, hypertension, and coronary artery disease. He underwent an MRI brain which revealed a T2 heterointense intra-axial right parietal lesion with significant perilesional edema. A provisional diagnosis of a cerebral abscess and malignancy was entertained. He was subjected to craniotomy and the surgical findings were consistent with a brain abscess and the pus was evacuated and sent for microbiological analysis. The pus fungal stain was consistent with septate hyphae and the cultures grew S. apiospermum . The histopathological findings were also consistent with a brain abscess caused by septate fungi ( Aspergillus like fungi). Results/Treatment: He was started on Liposomal Amphotericin B 5 mg/kg dose IV OD and injectable voriconazole. There was an initial clinical improvement with respect to sensorium and neurological status. He subsequently developed bradycardia with worsening sensorium to which he finally succumbed. Conclusion: Scedosporium apiospermum is an asexual form of Pseudoallescheria boydii, a fungus found in soil, contaminated water, and sewage. It is a rare cause of brain abscess in immunocompromised individuals. Near drowning or trauma may be the causative factors for immunocompetent individuals. Our patient was a well-controlled diabetic host with no apparent immunosuppression. Scedosporium apiospermum is diagnosed on the basis of culture and microbiological examination. Due to the similarities in the clinical and histopathological presentation of Scedosporium with other similar fungi, culture becomes the gold standard tool for diagnosis. Treatment includes surgical drainage of the abscess along with intravenous voriconazole for at least 8-12 weeks. The prognosis depends upon the immune status, surgical intervention, and medical antifungal therapy.